The effects of COVID‐19 lockdown on the body weight and lifestyle behaviors of U.S. adults. - Sung, Jaesang; Davis, Will; Qiu, Qihua (Southern Economic Journal, 2024)
The COVID‐19 pandemic and associated policies may have impacted body weight and related lifestyle behaviors. Using 2017–2020 Behavioral Risk Factor Surveillance System data, we estimate the effects of COVID‐19 lockdown on Body Mass Index (BMI) and the probability of obesity among adults in the United States. Our triple‐differences approach, using recent pre‐pandemic years as counterfactuals, identifies statistically significant lockdown‐induced increases in body weight. Event study results highlight a lagged effect of lockdown on body weight, with BMI increases manifesting 2 months post‐lockdown. These effects are particularly pronounced among non‐white adults, low‐income individuals, females, and metropolitan residents. The lockdown's impact on mental health, a potential mechanism driving BMI increases, is concentrated among non‐white, low‐income adults. We observe potential post‐lockdown changes in diet and sedentary behaviors, evidenced by increased Google searches for high‐calorie foods, food delivery apps, and video streaming. Google searches related to healthy habits, such as exercise, yield mixed results.